A plasmonic random laser tunable through stretching silver nanowires embedded in a flexible substrate. Issue 6 (14th February 2015) - Zhai, Tianrui; Chen, Jie; Chen, Li; Wang, Jieyu; Wang, Li; Liu, Dahe; Li, Songtao; Liu, Hongmei; Zhang, Xinping
<x xml:space="preserve">Abstract</x> A plasmonic random laser tunable through stretching silver nanowires embedded in a flexible substrate has been investigated.